Effectiveness of Premarital Counseling Implementation for Prospective Brides and Grooms at the Office of Religious Affairs - Fuqoha, Wahyu Saydul; Efendi, Faisal; Yusrial, Yusrial (Samara: Journal of Islamic Law and Family Studies, 2025)
The increasing number of divorce cases in Ranah Pesisir District indicates that many couples lack adequate readiness and maturity in building a household. This suggests that the implementation of premarital counseling at the Office of Religious Affairs in Ranah Pesisir District has not been fully effective or optimal, as regulated by the Director General of Islamic Community Guidance Decree No. 379 of 2018 concerning the guidelines for premarital counseling. This study employs a field research method with a qualitative approach. The data sources include primary data obtained through interviews with the Head of the Office of Religious Affairs in Ranah Pesisir District and prospective brides and grooms who have participated in premarital counseling, as well as secondary data from theses, journals, and books discussing premarital counseling. The findings of this study are as follows: First, premarital counseling is highly important and urgent to be implemented optimally, as it has a significant impact on the preparedness of couples entering married life. Second, the implementation of the premarital counseling program at the Office of Religious Affairs in Ranah Pesisir District has generally provided benefits to prospective couples, although it has not yet fully complied with the regulations outlined in the Director General’s Decree No. 379 of 2018. Third, based on the analysis of five effectiveness indicators, the implementation of the premarital counseling program at the Office of Religious Affairs in Ranah Pesisir District is considered fairly good, but not yet fully effective according to the applicable regulatory standards.